THE ENVIRONMENTAL COST IMPACT ON FIRM PERFORMANCE IN AVIATION SECTOR: DOES THE MANAGERIAL POWER REALLY MATTER - Anggrayni, Lilly (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the effect of environmental costs on company performance with managerial power as a moderating variable in the aviation sector in Indonesia. The research method used is quantitative with a regression approach using time series data from 2016 to 2023. The sample consists of eight airline companies that meet the purposive sampling criteria, namely companies that have published annual reports and sustainability reports for more than 10 years and explicitly disclose environmental costs. The results of the study indicate that environmental costs have a significant effect on company performance. Although managerial power is not significant individually, this variable together with environmental costs simultaneously affects company performance. However, managerial power is not proven to be a moderating variable that strengthens the relationship between environmental costs and company performance. The conclusion of this study emphasizes the importance of environmental cost disclosure and the strategic role of managers in driving corporate sustainability, in line with the Triple Bottom Line theory. Keywords: Environmental Cost, Firm Performance, Aviation Sector